2003
DOI: 10.1016/s0168-6496(03)00074-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale variation in spatial heterogeneity for microbial community structure in an eastern Virginia agricultural field

Abstract: To better understand the distribution of soil microbial communities at multiple spatial scales, a survey was conducted to examine the spatial organization of community structure in a wheat field in eastern Virginia (USA). Nearly 200 soil samples were collected at a variety of separation distances ranging from 2.5 cm to 11 m. Whole-community DNA was extracted from each sample, and community structure was compared using amplified fragment length polymorphism (AFLP) DNA fingerprinting. Relative similarity was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
180
3
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(200 citation statements)
references
References 48 publications
12
180
3
5
Order By: Relevance
“…The abundance and community compositions of the functional genes involved in denitrification can be affected by many factors, such as competition, predation, water content, pH, O 2 , and substrate availability (Ladd et al 1993;Franklin and Mills 2003). Some studies have investigated the responses of denitrifiers to soil environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…The abundance and community compositions of the functional genes involved in denitrification can be affected by many factors, such as competition, predation, water content, pH, O 2 , and substrate availability (Ladd et al 1993;Franklin and Mills 2003). Some studies have investigated the responses of denitrifiers to soil environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…To identify local factors that may influence the spatial distribution of diversity, including competitive interactions and resource availability, information on how phenotypes and genotypes are arrayed in space is crucial. There is a growing body of empirical studies examining the spatial distribution of genetic diversity in the soil at a range of spatial scales from micrometers to kilometers [3,8,20,25,48,56,69).…”
Section: Introductionmentioning
confidence: 99%
“…Soil community structures differ markedly between systems, and even across landscapes that appear macroscopically homogeneous. (for example, Axelrood et al, 2002;Franklin and Mills, 2003;Hackl et al, 2004;Sliwinski and Goodman, 2004;Oline, 2006;Herrera et al, 2007;Lamarche et al, 2007). Whole community studies and studies on the genotypes of individual taxa have revealed that, at high levels of taxonomic resolution, there is a degree of prokaryote endemism apparent across broad geographic scales (Fulthorpe et al, 1998;Cho and Tiedje, 2000;Wawrik et al, 2007).…”
mentioning
confidence: 99%